The Pragmatic Dimension of Perpetual Peace by Immanuel Kant - Nassar, Duaa; Aldababsa, Suzan (Jordan Journal of Social Sciences, 2024)
This paper adopts a study and analysis of the pragmatic dimension of Immanuel Kant’s "Perpetual Peace" project (1724-1804). It involves tracking the texts of the project with an analytical task aimed at reaching the practical feasibility of Kant’s peace principles, which focus on grounding the idea of peace through the connection between normative principles and political action. The paper addresses a fundamental issue: the possibility of a pragmatic dimension in Kant’s Perpetual Peace project, despite the implications associated with Kant’s rationalist propositions, which appear to be more concerned with theoretical concerns rather than practical outcomes. This is particularly challenging given Kant’s primary focus on intentions rather than results, posing a challenge in proving that Kant, in his political project, managed to achieve harmony between the foundational rules for global peace and their practical impacts. The paper aims to undertake an analytical task of Kant’s peace project texts, shedding light on Kant’s political intentions through these texts and revealing the moral spirit embedded within them, despite these rules being considered rational in nature. The paper concludes that there is a pragmatic dimension to Kant’s Perpetual Peace project, demonstrating that it has become a viable field for moral duty with possible practical results on the political and international levels.